Actuator fault diagnosis for flat systems: A constraint satisfaction approach - Seydou, Ramatou; Raissi, Tarek; Zolghadri, Ali; Efimov, Denis (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes a robust set-membership-based Fault Detection and Isolation (FDI) technique for a particular class of nonlinear systems, the so-called flat systems. The proposed strategy consists in checking if the expected input value belongs to an estimated feasible set computed using the system model and the derivatives of the measured output vector.
Keywords: fault detection; input observer; flat systems; consistency techniques